AMERICAN POLICY TOWARDS RUSSIA (1867-1895) - Malih, Khalid Razzaq; Kraidi, Zaman H. (ShodhKosh: Journal of Visual and Performing Arts, 2026)
U.S.–Russian relations between 1867 and 1895 underwent a notable shift, beginning with the Alaska Purchase, which helped foster a more positive atmosphere between the two countries. During this period, contacts between the American and Russian governments expanded across political, cultural, and economic spheres. At the same time, however, a major point of tension emerged in the form of the “Jewish Question,” particularly in relation to the Russian government’s treatment of American Jews and Jewish communities within the Russian Empire. Incidents of violence, forced displacement, and discriminatory policies drew criticism from the United States and brought increased attention to Russia’s domestic practices. Despite these challenges, relations between the two countries remained relatively stable. This stability is reflected in several developments, including the American humanitarian response to the famine that struck Russia between 1891 and 1893. The period also saw the conclusion of an important bilateral agreement—the Extradition Treaty—which carried significant political weight, especially in its provisions concerning the mutual surrender of individuals accused of political assassination. This study aims to explore the nature of U.S. policy toward Russia during this period, assessing its direction, outcomes, and broader implications through a historical analysis of the key events that shaped relations between the two states.